Localized organo-mineral fertilization maintains ultra-early watermelon yield while reducing mineral nitrogen input under temporary film cover - Ostonakulov, Toshtemir; Umirova, Durdona; Amirov, Xamidulla; Shamsiev, Anvar; Isaev, Sabirjan; Lukova, Iroda; Shabarova, Nilufar; Islamov, Anvar; Tuychiev, Shuxrat; Xakimova, Muabara; Amanturdiev, Ilhom (Frontiers in Agronomy, 2026)
Cultivating ultra-early watermelon (Citrullus lanatus) in arid continental climates requires both early-season thermal protection and efficient nutrient management to ensure high yield while limiting excessive mineral fertilizer inputs. This study, conducted during the 2022–2024 growing seasons in the Karshi steppe of Uzbekistan, evaluated the performance of five ultra-early watermelon hybrids under a temporary double-layer plastic film cover used as a background technology, while comparing conventional broadcast fertilization with localized organo-mineral fertilization applied per planting nest. A randomized complete block design was employed, testing five hybrids under identical film-covered conditions. Fertilization treatments included a standard broadcast application (10 t ha−1 manure + N150P120K75) and localized nest-based organo-mineral fertilization with reduced mineral NPK rates. Marketable yield, earliness, and fruit quality were assessed over three seasons. Localized fertilization significantly increased vegetative growth and marketable yield compared with broadcast application, despite a 30–40% reduction in total mineral nitrogen input. The hybrids Krimstar F1 and Montana F1 achieved the highest yields (26.1 and 25.4 t ha−1, respectively). Importantly, fruit quality was not adversely affected: total soluble solids (TSS) remained stable across treatments (7.4–7.5%), indicating that yield gains did not compromise internal quality. These results demonstrate that localized organo-mineral fertilization under temporary film cover can maintain high productivity of ultra-early watermelon while reducing mineral nitrogen inputs. The approach represents an agronomically efficient and environmentally safer fertilization strategy for early watermelon production in arid continental agro-ecosystems.